Incorporating informal workers into social insurance in Tanzania - Roosa Lambin; Milla Nyyssölä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Expansion of social protection reach among workers in the large informal economy represents a persisting and thorny challenge in the development context. In Mainland Tanzania, several domestically led policy reforms have been introduced to increasingly expand social protection for informal workers. This paper examines the case of Tanzania by exploring the policy developments that have sought to facilitate access to social protection within the informal economy over the past 10-15 years, notably through the expansion of social insurance provision. The paper highlights the pioneering legislative reforms and innovative approaches to social insurance adopted in the country, while drawing attention to the emergence of 'competitive' informal social security arrangements that attract informal workers at the expense of formal social insurance uptake. As such, the paper underscores the need for policy makers to double efforts in awareness-raising and policy design accounting for the needs and contribution capacities of informal workers.
Keywords: O17; N17; J65; H5; 330; informal sector; Tanzania; social policy; social insurance